Enhancing Software Development Efficiency: Scrum Framework in the MAMOI Project for Infusion Monitoring System - Huda, Achmad Torikul (Universitas Nurul Jadid, 2024)
MAMOI is an infusion monitoring system for hospitalized patients using a web-based application integrated with an IoT device that has a load sensor to monitor the remaining infusion water. The system aims to monitor the percentage of remaining infusion fluid in the infusion bag and know when to replace the infusion bag. In this research, the Agile Scrum method is applied to the development of MAMOI. This method was chosen because it can be adjusted to the needs and changes that occur during development. MAMOI development is divided into several sprints, each of which lasts two weeks. In each sprint, the development team focuses on developing predefined features. The results showed that the Agile Scrum method can be applied well in the development of MAMOI. The system can be completed within 4 months with good quality.